THE ROLE OF GUT MICROBIOME IN PREVENTION AND DEVELOPMENT OF ATHEROSCLEROSIS - Agnieszka Bajkacz; Katarzyna Piotrowicz; Hubert Piotrowicz; Jacek Kurzeja; Wojciech Kraśnik; Olga Jankowska; Anna Rogala; Joanna Osmólska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose. The gut microbiome has been the focus of scientific attention for many years. Modification of its composition are used in the prevention and treatment of many diseases. The aim of this review is to summarise the current knowledge about the role of the gut microbiome in cardiovascular diseases, using atherosclerosis as an example.Materials and methods. A literature review was carried out using the professional PubMed database. Articles were searched using keywords such as: "gut microbiome", "atherosclerosis", "diet", "physical activity".State of knowledge. The review describes the mechanism linking the gut microbiome to atherosclerosis and the differences in the composition of the gut microbiota in people with atherosclerosis risk factors compared with healthy individuals. The effect of probiotics on atherosclerotic lesions and the role of appropriate donor selection in faecal microbiota transplantation (FMT) are discussed. The review describes also how the composition of the gut microbiome affects physical performance.Summary. The gut microbiome plays a huge role in the human body. It affects the health of the entire body including the cardiovascular system. The composition of the intestinal microbiota varies between individuals. It has been found that the microbiome of people with risk factors for atherosclerosis is dominated by pro-inflammatory bacteria. The possibility of modifying the composition of the microbiome through diet, physical activity and the use of probiotics offers hope for the contribution of the gut microbiota to the prevention and treatment of atherosclerosis.